Exploring Accountability Practices in Village Financial Planning - Pande Gede Cahyana; Made Sudarma; Aji Dedi Mulawarman (Jurnal Ilmiah Akuntansi, 2024)
Accountability is essential for achieving sustainable results and involves a responsibility to fulfill mandated duties. This research reveals the practices of financial planning accountability in Peliatan Village, highlighting an underexplored area: the social and cultural dimensions of accountability in village financial management, especially in systems with dual governance. Employing an interpretive paradigm and ethnomethodological approach, the study examines the synergy between the formal and adat village governments. Accountability practices involve the participation of all stakeholder representatives in village meetings and are executed through a gradual process, starting with sangkepan deliberations at the dusun level. The village government prioritizes synchronizing long-term planning with annual work plans and ensuring compliance with official budget documents. These practices are essential components of village financial management, upheld through verification and validation at the sub-district level.